Resilience refused. Wasted potentials for improving food security in Dhaka - Keck, Markus; Etzold, Benjamin (ERDKUNDE, 2013)
In 2007 and 2008, Bangladesh was subject to a food crisis – the outcome of multiple causes – which had a severe impact on the urban poor of the country’s capital. Dhaka’s food supplies were repeatedly disconnected due to floods and cyclones, yet there was always enough food in the megacity thanks to wholesale traders’ diverse and flexible supply networks. Despite the interim government’s eviction drives aimed at slum dwellers and street vendors, the food hawkers still managed to distribute prepared food throughout the city. And despite rapidly rising food prices, most of the urban poor found ways to endure the crisis. In this article, we look at the people who made Dhaka’s food system resilient enough to avoid catastrophe. We discuss three relevant actor groups – food traders in wholesale markets, street food vendors, and poor consumers – and investigate the roles they play in keeping the city fed, and how they act in the light of crises. Neither these actors nor their contributions to urban food security are acknowledged by the state, nor are they substantially supported. Significant potentials for a resilient urban food system thus remain unpromoted and even blocked. Resilience is being refused.